PRINCIPLES OF MASLAHAH MURSALAH ON WOMEN'S EQUALITY AND JUSTICE: An Analysis towards Supreme Court Regulation of Republic of Indonesia Number 3 2017 Concerning with Guidelines for Adjudicating Women's Cases Against the Law - Endrik Safudin; Uswatul Khasanah (Kodifikasia, 2022)
Peraturan Mahkamah Agung Republik Indonesia Nomor 3 Tahun 2017 tentang Pedoman Mengadili Perkara Perempuan Berhadapan dengan Hukum lahir dimaksudkan untuk mewujudkan keadilan bagi perempuan agar mendapatkan akses yang sama atas sumber daya di dalam proses persidangan. Dengan kata lain, peraturan tersebut memuat ketentuan yang berkenaan dengan kontrol yang sejajar terhadap relasi antara laki-laki dan perempuan atas pemberian hak dan kewajiban khususnya pada proses persidangan sehingga keadilan substantif bagi perempuan dapat terwujud. Dengan kata lain, peraturan tersebut memberikan pedoman bagi hakim agar memberikan akses yang sama terhadap perempuan yang berhadapan dengan hukum, misalnya, akses pengambilan keputusan terhadap hak mendapatkan ganti kerugian, akses menjelaskan dampak kasus dan kebutuhan pemulihan. Dengan menggunakan penelitian kepustakaan (library research), penelitian ini akan menggali yaitu pertama, kesetaraan gender dan keadilan gender dalam prinsip maslahah mursalah. kedua, prinsip maslahah mursalah kesetaraan dan keadilan gender dalam Peraturan Mahkamah Agung Republik Indonesia Nomor 3 Tahun 2017 tentang Pedoman Mengadili Perkara Perempuan Berhadapan dengan Hukum. Ketiga, prinsip maslahah mursalah dalam Peraturan Mahkamah Agung Republik Indonesia Nomor 3 Tahun 2017 tentang Pedoman Mengadili Perkara Perempuan Berhadapan dengan Hukum. Hasil penelitian ini menunjukkan pertama, kesetaraan gender dan keadilan gender sejalan dengan prinsip maslahah mursalah. Kedua, prinsip maslahah mursalah kesetaraan dan keadilan gender sangat terakomordir oleh Peraturan Mahkamah Agung Republik Indonesia Nomor 3 Tahun 2017 tentang Pedoman Mengadili Perkara Perempuan Berhadapan dengan Hukum. Ketiga, Peraturan Mahkamah Agung Republik Indonesia Nomor 3 Tahun 2017 tentang Pedoman Mengadili Perkara Perempuan Berhadapan dengan Hukum dikonstruksikan dengan tujuan utuk merubah relasi kuasa sedemikian rupa antara laki-laki dan perempuan, baik dalam tataran pengetahuan maupun tindakan khususnya dalam ruang persidangan. [The Supreme Court Regulation of Republic of Indonesia Number 3 of 2017 concerning with the Guidelines for Adjudicating Women's Cases Against the Law is intended to create justice for women in order to have equal access on the resources in the trial process. In other words, the regulation contains provisions relating to equal control towards the relationship between men and women over the granting of rights and obligations, especially in the trial process, so that substantive justice for women can be realized. In other words, the regulation provides guidelines for judges to provide equal access to women conflicting with the law, for example, access to decision-making on the right to compensation, access to explain the impact of cases and the need for remedies. By using library research, it will explore, firstly, gender equality and gender justice in the principle of maslahah mursala; secondly, the principle of maslahah mursalah on equality and gender justice in the Regulation of the Supreme Court of the Republic of Indonesia Number 3 of 2017 concerning with the guidelines for Adjudicating Women's Cases with the Law; thirdly, the principle of maslahah mursalah in the Regulation of the Supreme Court of the Republic of Indonesia Number 3 of 2017 concerning with guidelines for Adjudicating Women's Cases conflicting with the Law. The results of this study show that first, gender equality and gender justice are in line with the principle of maslahah mursalah, second, the principle of maslahah mursalah on equality and gender justice is accommodated by the Regulation of the Supreme Court of the Republic of Indonesia Number 3 of 2017 concerning with the Guidelines for Adjudicating Women's Cases Against the Law, third, the Regulation of the Supreme Court of the Republic of Indonesia Number 3 of 2017 concerning with the Guidelines for adjudicating women's cases against the law are constructed with the aim of changing power relations in such a way between men and women,at the level at both knowledge and action, especially in the courtroom.]